Benchmark dataset for hydraulic simulations of flash floods in the French Mediterranean region - J. Godet; J. Godet; P. Nicolle; N. Hocini; E. Gaume; P. Davy; F. Pons; P. Javelle; P.-A. Garambois; D. Lague; O. Payrastre (Earth System Science Data, 2025)
The absence of validation or comparison data for verifying flood mapping methods poses a significant challenge in developing operational hydraulic approaches. This article aims to address this gap by presenting a benchmark dataset for flash flood mapping in the French Mediterranean region. The dataset described in this paper (https://doi.org/10.57745/IXXNAY, Nicolle et al., 2024) includes flood hazard maps and simulation results of three actual flash flood events, all computed in a steady regime at a 5 m resolution using a 2D SWE (shallow water equation) model (neglecting inertia) named Floodos (Davy et al., 2017). Additionally, it includes the input data necessary (digital terrain models, inflow discharges, hydrographic network) for conducting similar simulations with other hydrodynamic modelling approaches in both steady and unsteady regimes. A comprehensive validation dataset, comprising observed flood extents, high water marks, and rating curves, is also provided, enabling a detailed evaluation of 2D hydraulic simulation results. The simulation results from Floodos, compared against stage–discharge rating curves available at gauging stations, yielded highly encouraging outcomes. The median error (sim.–obs.) was −0.04 m for the 2-year return period and −0.14 m across all simulated return periods, ranging from 2 to 1000 years.